Research on Park Landscape Design Strategy Based on Urban Cultural Brand -- A Case Study of Xinyang City - Zhang, Wei; Lamat, Mastika b. (Journal of Ecohumanism, 2024)
This paper aims to explore the strategy of park landscape design based on urban cultural brand, taking Xinyang City of China as an example to conduct in-depth research. First, the paper analyzes the historical and cultural background, regional characteristics and the importance of Xinyang city brand construction. Through combing the unique natural resources and cultural landscape of Xinyang, it is proposed that the park landscape design should fully integrate the local cultural elements to enhance the cultural identity of the city. Secondly, the paper discusses the core strategy of park landscape design, mainly including the implantation of cultural symbols, and displaying Xinyang's cultural characteristics through landmark buildings and art installations; The protection and promotion of ecological environment, combined with the local natural landscape, to create a harmonious ecological space; The design method of community participation encourages residents to participate in the planning and construction of the park to enhance the sense of community belonging. Finally, through the case analysis, it shows how successful park landscape design can enhance the cultural brand of the city, promote the development of tourism and improve the quality of life of citizens. The research results show that park landscape design based on urban cultural brand can not only enrich the cultural connotation of the city, but also provide new impetus for the sustainable development of the city.